Perencanaan Aplikasi Pembayaran Siswa Barcode Reader di MTs Karangawen Kabupaten Demak - Maulana Fikri; Bagas Santoso (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2023)
Karangawen State Madrasah Tsanawiyah (MTs) is a junior secondary level formal education institution which is geographically located in Karangawen Village, Karangawen District, Demak Regency, with a total of around 800 students divided into 25 classes. This Madrasah has been officially established since 1997. With a large number of students, MTs Negeri has been supported by facilities and infrastructure capable of supporting the process of teaching and learning activities as well as administrative activities. Currently MTs Negeri Karangawen already has 20 units of computers in one computer laboratory equipped with a computer network to support teaching and learning activities. In the field of administration, it has also been supported by 5 units of computers that are used by administrative staff in order to serve all teaching and learning process activities, including in the service of student financial payments.